Efficiency Assessment of an Inverter based on Solar PV Energy in Baghdad - Nasir, Bilal (Engineering, Technology & Applied Science Research, 2024)
The yearly energy yield of a Solar Photovoltaic (SPV) system is a rendition pointer utilized by the erector to determine the output energy generated by it. From the energy speculation, the payback period and the return on investment can be contemplated. The system energy yield formula consists of many parameters, the most important of which is the SPV inverter efficiency. The European and peak (maximum) efficiency factors from the inverter data sheet are typically utilized, but this utilization is unsound because the SPV does not always work at the peak of its effectiveness due to varying irradiance. The inverter’s weighted efficiency is considered more sound as it deems the inverter output power peculiarities. The European weighted efficiency is the most widely accepted inverter efficiency determination. Since it is derived and documented on a rimmed European irradiance profile, it may not be appropriate for inverters constructed in different climatic conditions, especially in the equatorial and subtropical environmental regions. This work aims to formulate a fangled weighted efficiency equation for the inverter’s work in the Iraqi environment (especially in Baghdad city as a case study) documented on the IEC 61683: 1999 Standard and Irradiance-Duration curve. The sophisticated formula is endorsed on experimental data from the field using an SMA-SB-4000-TL inverter. It was found that the speculated energy yield using the derived efficiency formula for the Baghdad environment closely matches the energy yield of an original 4.0 KW SPV inverter system with only 1% difference between the determined and acquired values. This means that the employment of the Baghdad weighted efficiency in place of the European or peak weighted efficiency will result in a sounder speculation of the system energy yield, return on investment, and payback duration of the SPV system project.